Colesional cutaneous talaromycosis (penicilliosis) and Kaposi sarcoma in an HIV-infected patient - Lai, Shau Kong; Tan, Lii Jye; Hussin, Huzlinda; Salleh, Amizatul Aini; Bakrin, Ikmal Hisyam (Wiley Open Access, 2021)
HIV-infected patients are at high risk of multiple pathologies. Accurate identification of multiple colesional pathologies is critical for the patient management. We report a distinctive case of colesional cutaneous talaromycosis and Kaposi sarcoma. Prudent histopathological examination and judicious use of adjunct diagnostic test are essential for the diagnosis.